Financial Investment Opportunities and the Macroeconomy. - Chen, Nai-Fu (Journal of Finance, 1991)
This paper studies the relation between changes in financial investment opportunities and changes in the macroeconomy. States variables, such as the lagged production growth rate, the default premium, the term premium, the short-term interest rate, and the market dividend-price ratio, are shown to be indicators of recent and future economic growth and positively correlated with expected future economic growth. These results offer straightforward interpretations of recent evidence on the forecasts of the market excess return by state variable via their forecasts on the macroeconomy.